Implementation deficit in social sector: Mismatch between goals and outcomes - Ramabrahmam, I.; Babu, J. Ravindra (2005)
Constitution makers visualised that certain ideals particularly in the economic domain should not be given up by the state. The union, state and local governments have a moral obligation to follow. The directive principles in the Constitution of India stand as a testimony to the framers' articulation. These broadly can be stated as those which stand for the welfare of the people. It includes education, health and nutrition. Post-reform period offers a challenge to the students of public policy as to how nation-states which accepted the structural adjustment programmes effected changes in their welfare domains. It was argued by champions of the liberalisation that withdrawal of state from the other economic sectors, in fact, allows the nation states, a greater elbow room for the social sector. This assumption needs to be analysed against the backdrop of not only dwindling budgetary support to welfare across the states in India, but also from the perspectives of how allocated resources are efficiently used. -Reproduced.
Keywords: Economic and social development; Social sector